Nonsense-mediated decay mechanism is a possible modifying factor of clinical outcome in nonsense cd39 beta thalassemia genotype - Maria Concetta Renda; Angela Vitrano; Massimo Attanasio; Emanuela Fecarotta; Angela Piazza; Antonino Giambona; Germana Fiorentino; Disma Renda; Paolo Rigano; Giuseppina Calvaruso; Filippo Cassarà; Aurelio Maggio (Thalassemia Reports, 2012)
Nonsense-mediated mRNA decay (NMD) is a surveillance system to prevent the synthesis of non-functional proteins. In β-thalassemia, NMD may have a role in clinical outcome. An example of premature translation stop codons appearing for the first time is the β-globin cd39 mutation; when homozygous, this results in a severe phenotype. The aim of this study was to determine whether the homozygous nonsense cd39 may have a milder phenotype in comparison with IVS1,nt110/cd39 genotype. Genotypes have been identified from a cohort of 568 patients affected by β-thalassemia. These genotypes were compared with those found in 577 affected fetuses detected among 2292 prenatal diagnoses. The nine most common genotypes, each with an incidence rate of 1.5% or over, and together accounting for 80% of genotype frequencies, underwent statistical analysis. Genotype prevalence was calculated within the overall group. Results are expressed as proportions with 95% confidence intervals; P≤0.05 was considered statistically significant. A binomial distribution was assumed for each group; z-tests were used to compare genotype frequencies observed in the patient group with frequencies in the affected fetus group. In the absence of selecting factors, prevalence of these two genotypes was compared between a cohort of 568 β-thalassemia patients (PTS) and 577 affected fetuses (FOET) detected during the same period. IVS1,nt110/cd39 was significantly more prevalent in FOET than PTS (P<0.0001), while there was no significant difference in prevalence of cd39/cd39 in FOET compared with PTS (P=0.524). These results suggest a cd39 genotype NMD mechanism may be associated with improved clinical outcomes in thalassemia major. 无义介导的mRNA 降解（NMD）   是一种预防非功能性蛋白质合成的监控系统。在β地中海贫血中，NMD可能对临床结果有影响。第一次出现的过早终止密码子（PTC）为β珠蛋白cd39突变；若为纯合子，则会导致严重的表型。 本研究旨在确定与IVS1,nt110/cd39基因型相比，纯合子无义cd39能否有更轻度的表型。目前已确定568名β地中海贫血患者的基因型，并与从2292个产前诊断中检测出的577名地中海贫血胎儿的基因型相比较。对9个最常见基因型进行统计分析，每个基因型的发生率均为1.5%或以上，共占基因型频率的80%。在整个组中计算基因型分布情况，其结果以95%置信区间表示；若P≤0.05，则具有统计意义。各组均假定成一个二项分布；Z测试适用于比较患者组的基因型频率和地中海贫血胎儿的基因型频率。 若没有选择因子，则比较568名β地中海贫血患者（PTS）和同一时期所检测到的577个地中海贫血胎儿（FOET）这两组基因型的发生率。IVS1,nt110/cd39在FOET中的发生率明显高于PTS（P<0.0001），同时cd39/cd39 在FOET和PTS（P=0.524）中的发生率并没有明显不同。这些结果表明cd39基因型NMD机制可能与重型地中海贫血的临床结果相关。